Fast single‐beam‐CARS imaging scheme based on in silico optimization of excitation phases. (20th May 2015) - Wipfler, Alexander; Buckup, Tiago; Motzkus, Marcus; Joubert, Pierre; Lavorel, Bruno; Kiefer, Johannes; Moger, Julian
<x xml:space="preserve">Abstract</x> A novel scheme for the detection of known species with single‐beam coherent anti‐Stokes Raman scattering spectroscopy is presented in theory and simulations. The introduction of a simulation tool based on fast Fourier transforms allows a purely numerical optimization of excitation phases ex situ, to which we refer to as in silico optimization. Such an optimal phase is based on the encoding of vibrational resonances in specific spectral detection windows using multichannel measurements. The presented detection scheme offers a route to fast chemical selective imaging with high contrast and simplified data acquisition, thereby avoiding photodamage of sensitive biological samples. Copyright © 2015 John Wiley & Sons, Ltd.